ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2011-2013 - Wahyuning Astuti, 12.05.52.0184; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This research aims to examine the effect of GDP, total population, total tourist, and total hotel to local revenue (PAD) at the District / town in Central Java Province. The source of data that used is secondary data that obtained from BPS Central Java Province from year 2011 to 2013. The sampling technique using sensus. Mechanical testing data is to use a multiple linear regression analysis. The results of research show that each of variable has the same effect which is variable Gross Regional Domestic Product (GDP), number of tourist and number of hotel effect sisignificantly positive to local revenue (PAD). While the variable of total population is not affected to total revenue (PAD).Keywords: PAD, GDP, Total Population, Number Of Tourist, Number Of Hotel